Financial management and sustainability practices: evidence from the top 100 global sustainable firms / Rashid Ameer … [et al.] - Ameer, Rashid; Othman, Radiah; Atan, Ruhaya; Mat Isa, Rosiatimah (Research Management Institute (RMI), 2010)
This research investigates the relationship between investment and financing policies of the top 100 global organizations and the impact of these policies on their financial performance. Our findings shows that the US and UK corporations rely excessively on internal finance compared to the Japanese corporations that rely on external finance for sustainable development We examined the sustainable practices using four indexes- community, diversity, environment and ethics. We found that the European corporations lead in all four dimensions of sustainable practices. Based on four indexes, though our results showed no significant differences related to return on assets, profit before taxes, and cash flows from operations between corporations with superior community, diversity, and ethical practices and those without such superior practices. However, there was a significant difference in sales growth of corporations with superior community practices compared to those without such practices. We found significant differences related to profit before taxes and cash flows from operations between corporations with superior environmental practices and those without such superior practices. Our research has economical and social policy implications for the developed and developing countries' corporations, regulators, and policymakers.